Development of Problems-Based Computer Assisted Instruction on Waste Material and Its Effect on Students Problem Solving Ability - Iyoh Maspiroh; Bambang Subali (Journal of Science Education Research, 2019)
This study aimed to develop problems-based computer-assisted instruction in biology learning on waste material and its effectiveness on the ability of learners to solve the problem. This research was adapted from the model of development that includes ADDIE analyze, design, develop, implement, and evaluate. Test subjects in this study were the students of grade X at SMA Negeri 1 Magelang. Data were collected through questionnaires, observations, and test of problem-solving skills. The results showed that computer-assisted instruction effectively used to practice problem-solving. This was seen in the mode and the mean on experimental class higher than the control class. It was also seen at Anacova test followed by t-test at the 0.05 significance level result that media used in the experimental class were able to show better achievement than traditional learning in control class.